A165 INVASIVE GASTRIC MUCORMYCOSIS - CASE REPORT OF A RARE CAUSE OF UPPER GASTROINTESTINAL BLEEDING. (15th March 2019) - Yusuf, A; Castellani, L; Xiong, X; Muller, M; May, G
Abstract: Background: Mucormycosis is a rare but potentially life threatening fungal infection. Typically presenting as a rhino-orbital-cerebral infection in severely immunocompromised patients, it less commonly causes infection of the gastrointestinal tract. Aims: This report outlines the rare case of a patient with multiple myeloma who presented with upper gastrointestinal bleeding secondary to gastric mucormycosis, including the diagnosis, treatment plan, and hospital course. The existing evidence regarding the incidence, diagnosis, treatment, and prognosis of gastrointestinal mucormycosis is discussed. Methods: Case report, review of literature. Results: A 51-year-old immunocompromised male was hospitalised with severe pneumonia, requiring intubation due to respiratory failure. Medical history included a 13-year history of multiple myeloma with recurrence despite 3 stem cell transplants and multiple courses of chemotherapy. He had underlying renal dysfunction and deep vein thrombosis on therapeutic anticoagulation. He developed upper gastrointestinal bleeding with a supra-therapeutic INR of 6.5, and despite reversal agents and blood transfusions, he continued to bleed. Upper endoscopy demonstrated a poorly distensible stomach with diffuse abnormal greyish thickening from the gastric cardia to mid-antrum, which was rubbery, friable and had signs of oozing blood. Biopsies and cultures showed broad fungal hyphae consistent with Mucormycosis. The Infectious Diseases service was consulted, and the patient was started on Liposomal Amphoteracin B. Conclusions: Mucormycosis is a rare (0.43–1.7 per million) infection, acquired via inhalation or direct skin inoculation of fungal sporangiospores that are ubiquitous in nature, likely found in decaying organic matter. Infection may clinically manifest as rhinocerebral/sinusitis, pulmonary, cutaneous, or gastrointestinal invasion. Gastrointestinal infection is exceedingly rare (roughly 6% of cases) and may present as an abdominal mass, upper GI bleed, local infiltration, or gastric perforation. Roughly a quarter of cases progress to disseminated infection. Risk factors include hematological malignancy, stem-cell transplant, and diabetes. Diagnosis is primarily based on characteristic histopathology, as biopsy cultures often did not grow adequately; however, PCR of 18S ribosomal DNA may provide greater diagnostic accuracy. No definitive treatment protocol exists, but patients have been treated with Amphoteracin B +/- surgical resection, and some patients have been treated with oral Posaconazole after local disease control. No long-term prognosis data exists, but one study reported death in 16 of 28 patients shortly after diagnosis. Well demarcated area transitioning from normal mucosa to abnormal greyish thickening; poorly distensible stomach, rubbery, friable, with oozing mucosa from the cardia to mid-antrum. Funding Agencies: None